Frequency of Allergic Reactions in Cancer Patients - Anjum, Ali; Salman, Umer; Muhammad Arslan (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of allergic transfusion reactions among patients suffering from cancer receiving blood and blood component transfusions. Study Design: Descriptive cross-sectional study. Place and Duration of Study: This study was conducted at a tertiary care hospital from 17 January 2025 to 17 May 2025. Methodology: A total of 150 diagnosed cancer patients of both genders who received blood or blood component transfusions were included using non-probability consecutive sampling. Patients were monitored during and after transfusion for signs of allergic transfusion reactions. Data regarding demographic characteristics, type of malignancy, treatment modality, blood components transfused, and transfusion reactions were recorded. Statistical analysis was performed using SPSS, and results were expressed as frequencies, percentages, mean, and standard deviation. Results: The mean age of patients was 55.48 ± 7.31 years, with a male predominance (56%). Allergic transfusion reactions were observed in 82 patients (54.7%). Urticaria (20.7%) was the most common presentation, followed by pruritus (12.0%) and skin rash (10.0%). A statistically significant association was found between type of malignancy and allergic transfusion reactions (p = 0.044), while no significant association was observed with age, gender, treatment modality, type of blood component, or number of transfusions. Conclusion: Allergic transfusion reactions are frequent among cancer patients receiving blood transfusions. Although most reactions are mild, their high occurrence necessitates careful monitoring and adoption of preventive transfusion strategies to improve patient safety.